Islamic Religious Education Curriculum Development Model - Hasriadi; Siswanto; Muktamar, Ahmad (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The field of education is ever-evolving and always changing in the direction of perfection, both in terms of future readiness and adaptability to the environment and time in which it exists. In essence, the curriculum serves as a roadmap for carrying out the educational process in both schools and even colleges. There is no denying that curriculum implementation in the millennial era requires curriculum to change to meet the demands of the times. Islam itself strongly encourages movements for constructive development and change, believing that these are the keys to advancement and improvement. This problem served as the foundation for the formation of the research problem, which is the idea and framework for creating an Islamic religious education curriculum. Reference-based research—that is, observation centered on books, journals, or other publications—is the methodology employed. The study's findings demonstrate the curriculum's function in a number of areas that are important to educational activities, such as a) the school in question; b) schools or madrasas above it; and c) the community, which uses graduates. An eclectic method, or selecting the best of the four techniques listed below, can be used to build an Islamic religious education curriculum that fits its unique features. These methods include the following: a) subject-based methods; b) humanistic methods; c) technology methods; and d) social reconstruction methods. In the meantime, the Islamic education curriculum development model provides two alternatives for madrasas, including a competency-based and life skills-based curriculum development model and an Islamic Religious Universities competency-based curriculum development model.